2014
DOI: 10.1007/s11605-014-2476-6
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management and Long-Term Follow-Up of Solid Pseudopapillary Tumor of Pancreas: A Large Series from a Single Institution

Abstract: Complete resection of the tumor is associated with good survival, even in patients with vessel involvement or metastases. In patients with tumor recurrence, a second resection resulted in long-term survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
18

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 24 publications
2
38
0
18
Order By: Relevance
“…This patient then presented with recurrent pancreatic head SPN and underwent a PD at a PSORC institution and had no recurrence after PD. Enucleation is a technique that can be used for SPN pathology in a subgroup of patients with the proper anatomic relations 22‐26 . A head of the pancreas mass is usually very close to the portal vein/SMV, bile duct, and pancreatic duct; therefore, successful enucleation with a negative margin may not be possible.…”
Section: Discussionmentioning
confidence: 99%
“…This patient then presented with recurrent pancreatic head SPN and underwent a PD at a PSORC institution and had no recurrence after PD. Enucleation is a technique that can be used for SPN pathology in a subgroup of patients with the proper anatomic relations 22‐26 . A head of the pancreas mass is usually very close to the portal vein/SMV, bile duct, and pancreatic duct; therefore, successful enucleation with a negative margin may not be possible.…”
Section: Discussionmentioning
confidence: 99%
“…23 However, complete, aggressive surgical resection should be performed for these neoplasms even in the presence of invasion into adjacent organs and distant metastases based on the prolonged survival after complete surgical resection. 24,25 Cheng and colleagues reported that en bloc synchronous portal vein-superior mesenteric vein or adjacent organ resection should be carried out to achieve a complete resection. 26 In our study, most patients who had pancreatic parenchyma infiltration or vascular invasion with R0 resection did not develop local recurrence or distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The biological behavior and prognosis of SPNs are still difficult to predict, and pancreatic SPN is still an enigma [14,15]. Surgery remains the mainstay of therapy [6,7,16], but selection of surgical approaches is still under debate. Some authors have advocated function-preserving surgical approaches [7,10], while others favor aggressive surgical resection [17] or have considered parenchymapreserving resection as a significant risk factor for tumor recurrence [8].…”
Section: Introductionmentioning
confidence: 99%